Teaching portfolio: Français - Buckley, Lydia (Kansas State University, 2008)
This portfolio presents demonstrably proven effective guidelines for classroom activities in accordance with the widely accepted, communicative approach to teaching foreign languages. Stemming from the author's own personal experience with eighth-grade French students, these examples are based on the standard principles of Communicative Language Teaching. As graphically and comprehensively illustrated in this portfolio with student-friendly, image- and table-enhanced templates, the author identifies and explains how structured input and output activities might be developed to encompass the four components of teaching a language: namely, listening; reading; writing; and speaking. Beyond the objective of showing the usefulness of this teaching/learning method through examples of structured activities, the author augments the portfolio with valuable associated teacher's materials including a current professional teaching CV, a philosophy of teaching statement, a working syllabus, a classroom management plan, and a rationale for the activities included -- all of which are applicable to typical classroom environment situations. These carefully constructed worksheets and visuals are amply and appropriately interspersed throughout the sectional contents of the portfolio, thereby adding to the understanding of the textual descriptions of recommended teacher and student activities. In this manner, the author has documented a tested and practical set of working materials designed to promote the facility, ease and enthusiasm of learning languages from both the teacher and student points-of-view and needs. The compartmentalized contents of this portfolio, organized into 13 sections as listed in the table of contents, comprise a wide range of actual classroom activities that evolved from the author's daily teaching experiences. The portfolio instructions and examples also incorporate the well-founded and well-known teaching techniques documented in the professional literature as cited throughout the narrative text. For this purpose then, this portfolio delivers a complete and thorough description of possible teacher and student activities in various foreign language classroom scenarios.
Keywords: French; Teaching; Portfolio; Education, Language and Literature (0279); Language, Modern (0291)